2015
DOI: 10.1371/journal.pbio.1002153
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Derived Phospholipids Control Synaptic Neurotransmission and Plasticity

Abstract: Synaptic communication is a dynamic process that is key to the regulation of neuronal excitability and information processing in the brain. To date, however, the molecular signals controlling synaptic dynamics have been poorly understood. Membrane-derived bioactive phospholipids are potential candidates to control short-term tuning of synaptic signaling, a plastic event essential for information processing at both the cellular and neuronal network levels in the brain. Here, we showed that phospholipids affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 61 publications
5
94
0
Order By: Relevance
“…They detected presynaptic glutamate release when stimulating LPAR localized in the presynaptic terminals, whereas excessive LPA stimulation was found to cause seizures (Roza et al, 2019). These results are in line with the observation that LPA modulates the excitatory as well as the inhibitory synapses to regulate synaptic strength and neuronal activity (García- Morales et al, 2015). It has been demonstrated that LPA functions as a dual regulatory factor in modulating synaptic excitability.…”
Section: Lpa and Neuroplasticitysupporting
confidence: 61%
See 2 more Smart Citations
“…They detected presynaptic glutamate release when stimulating LPAR localized in the presynaptic terminals, whereas excessive LPA stimulation was found to cause seizures (Roza et al, 2019). These results are in line with the observation that LPA modulates the excitatory as well as the inhibitory synapses to regulate synaptic strength and neuronal activity (García- Morales et al, 2015). It has been demonstrated that LPA functions as a dual regulatory factor in modulating synaptic excitability.…”
Section: Lpa and Neuroplasticitysupporting
confidence: 61%
“…High levels of LPA have been shown to lessen the size of available vesicle pools at glutamatergic pre-synaptic neurons, thus providing negative feed-back to prohibit the transmission at excitatory synaptic terminals. Nevertheless, in the presence of low concentrations of LPA, inhibitory postsynaptic receptors, namely gamma-aminobutyric acid receptor type A (GABAAR), were internalized to restrain transmission at inhibitory synaptic terminals, thereby briefly increasing the synaptic excitability (García- Morales et al, 2015;Roza et al, 2019). In line with these findings, it is believed that LPA plays a crucial role in modulating glutamatergic transmission in the nervous system.…”
Section: Lpa and Neuroplasticitymentioning
confidence: 92%
See 1 more Smart Citation
“…Tomosyn2 controls acetyl choline release from cholinergic nerve terminals (Geerts et al., 2015) and acetylcholine (ACh) is known to induce persistent γ-oscillations in the hippocampus (Picciotto et al., 2012). LysoPLD/ATX encodes one of the major enzymes involved in synthesis of lysophospatidic acid (LPA), a molecule with a key signaling role controlling both excitatory and inhibitory synapse functions (García-Morales et al., 2015, Vogt et al., 2015). LPA has a critical role in the nervous system: knockout of LPA1 receptor causes anxiety (Santin et al., 2009), which also characterizes the Slm2 mouse, and LysoPLD/ATX is essential for brain development (Greenman et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these indirect mutual effects of lipids and signaling, many lipids exert bioactive properties directly as cellular signals and 2nd messengers (for reviews, see Hannun and Obeid, 2008; García-Morales et al, 2015; Morales-Lázaro and Rosenbaum, 2015). In this study, we have focused attention on fatty acyls (for review see Divito and Cascio, 2013).…”
Section: Introductionmentioning
confidence: 99%